Strain Gauge Evaluation of Transfer Impression Techniques of Multiple Implant-Supported Prosthesis - Nishioka, Renato Sussumu [UNESP]; De Santis, Leandro Ruivo [UNESP]; De Melo Nishioka, Gabriela Nogueira [UNESP]; Kojima, Alberto Noriyuki [UNESP]; Souza, Francisley Avila [UNESP] (Lippincott Williams & Wilkins, 2018)
Purpose: This in vitro study assessed the accuracy of multiple implant-level impression techniques (open tray and closed tray) for the fabrication of 3-unit implant prostheses with strain gauge (SG) analysis. Materials and Methods: A polyurethane master model was designed to simulate a clinical situation. Two rigid custom trays were fabricated for the model. The impression material used was polysulfide. Transfer implant impressions were made using 2 techniques; ten tapered copings not splinted (custom closed tray) and ten square copings splinted with acrylicresin (custom open tray). The improved stone models were allowed to set for 1 hour before being separated from the impression. The superstructures were sprued, invested, and cast with a cobalt-chromium alloy. Four SGs were bonded on the surface of each polyurethane block. Results: A statistically significant difference was found between the 2 impression techniques tested (P = 0.000). This study found a significant average difference of 144.68 +/- 5.53 mu epsilon for open custom tray and 253.3 +/- 16.7 mu epsilon for closed custom tray. Conclusion: The custom open tray technique was the most accurate impression for multiple implants compared with closed custom tray.
Keywords: dental prosthesis; biomechanics; dental implants